Contribution of Surface Distributions to Constant-Phase-Element (CPE) Behavior: 1. Influence of Roughness. (10th August 2015) - Alexander, Christopher L.; Tribollet, Bernard; Orazem, Mark E.
Abstract: Finite–element simulations were used to calculate the influence of surface roughness of V-shaped grooves on the impedance of ideally polarized disk electrodes. The characteristic length associated with roughness was found to depend on the width or period of the roughness as well as the roughness factor. The characteristic dimension associated with a rough disk was shown to be the disk radius multiplied by the roughness factor. This work shows that for small roughness factors, while roughness causes frequency dispersion, the frequency dispersion is seen only at frequencies that are much higher than those associated with the disk geometry. Thus, a constant–phase element associated with a surface distribution of time constants cannot be attributed to surface roughness.